Examination of the Legal Status of Contracts Containing Automatic Renewal Clauses in Iran: A Comparative Analysis with French and English Law - Alireza Shamshiri; Fereshteh Amirabadi Farahani (پژوهشنامه حقوق تطبیقی)
In some contracts, a condition known as the contract extension condition is included due to contractual necessity. This condition allows the parties to avoid the need to renegotiate or conclude a new contract. However, this privilege is not immune to challenges and should be examined through a comparative study of the French and English legal systems. However, at times, the performance of an extended contract may encounter hardship or become impossible due to changes in contractual circumstances. In some instances, one party may exploit its superior position. These situations can serve as barriers to the implementation of the automatic contract extension clause. In both English and French law, various legal theories are employed, including "Change of Circumstances" (Rebus sic stantibus), "Frustration" and "Force-majeure" and the "Abuse of Right. In the comparative study conducted using an analytical-descriptive method and by referencing library sources in Iranian law, it is possible to adhere to general principles such as “La-Zarar” (no-harm rule) and " Osr VA Haraj " (rule of hardship), " Ghabne Hades " (sudden contractual lesion), and the prohibition of the abuse of rights offer solutions that are comparable to those found in the legal systems of England and France. These include the modification of extended contracts and, in certain cases, the cancellation of extension conditions and the non-implementation of extended contract.